Logística, sistemas de movimento, fluxos econômicos e interações espaciais no território Paulista: Uma abordagem para a geografia dos transportes e circulação - Silveira, Márcio Rogério [UNESP] (My University, 2009)
This work aims to express the production and consumption changes occurred in the State of São Paulo in line with the logistics, the systems of movement and the economic flows. The mentioned productive and consumption devolutions towards the interior just was possible in the fast rhythm, with the hierarchical combination of some basic elements, such as: 1) the logistics as strategy, planning and management (including in the concession of public services to the private enterprise) of transports, storage and communications; 2) the technological improvement of systems of movement (infrastructure and means of transportation) and 3) the economic flows (goods, services, informations, capital gains and people) in the territory. Thus, we go to an analysis of the impacts of the fifth logistics revolution and the alternatives between systems of movement and territorial fluidity in the service of corporative demands in the space pertaining to the State of São Paulo. © Copyright Scripta Nova, 2009.
Logistics, systems of movement, economic flows and spacial interactions in the space pertaining to the State of São Paulo: An approach to the Geography of Transports and Movement
Keywords: Economic flows; Logistics; São Paulo; Systems of movement